2017
DOI: 10.1007/s10198-017-0873-y
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of diabetes to French national health insurance: a new cost-of-illness method based on a combined medicalized and incremental approach

Abstract: A better understanding of the economic burden of diabetes constitutes a major public health challenge in order to design new ways to curb diabetes health care expenditure. The aim of this study was to develop a new cost-of-illness method in order to assess the specific and nonspecific costs of diabetes from a public payer perspective. Using medical and administrative data from the major French national health insurance system covering about 59 million individuals in 2012, we identified people with diabetes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 28 publications
(32 reference statements)
3
32
0
Order By: Relevance
“…The mean annual medical cost per capita was €3086, consistent with the results of other studies conducted in Italy or in Europe [7,8,11,23,32]. However, the median annual medical cost (€1012) is a more accurate summary measure because the distribution of costs is skewed, with a few patients accounting for a large proportion of costs, in line with other studies [10,12]. We confirmed that hospitalization accounts for the large majority of costs (53.1%) followed by drugs (29.5%) and outpatient services (17.4%) [7,8,11,23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean annual medical cost per capita was €3086, consistent with the results of other studies conducted in Italy or in Europe [7,8,11,23,32]. However, the median annual medical cost (€1012) is a more accurate summary measure because the distribution of costs is skewed, with a few patients accounting for a large proportion of costs, in line with other studies [10,12]. We confirmed that hospitalization accounts for the large majority of costs (53.1%) followed by drugs (29.5%) and outpatient services (17.4%) [7,8,11,23].…”
Section: Discussionsupporting
confidence: 89%
“…The principal cost components are hospital and outpatient care, even if drug costs are becoming more relevant since the introduction of the expensive analog insulins and incretinbased agents and sodium-glucose cotransporter 2 (SGLT-2) inhibitors [9]. Many studies and systematic reviews [8,[10][11][12][13][14][15][16][17] have evaluated healthcare costs incurred by a population with diabetes using a cost-of-illness approach that includes all direct and indirect costs related to lost productivity. A recent systematic review [3] showed that the annual direct costs of diabetes per patient in international dollars, regardless of the costing method applied and the cost components included, range from $242 in Mexico in 2010 [18] to $11,917 in a study conducted in the USA in 2007 [19], while indirect costs range from $45 for Pakistan in 2006 [20] to $16,914 for the Bahamas in 2000 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the global comprehensive approach, used in this analysis, includes all the expenditures incurred by a population with a particular disease. 13 These expenditures are not necessarily related to the disease of interest; for instance, expenditures related to orthopaedics surgery or cancer treatment incurred by a patient with AF will count towards the global comprehensive cost of AF.…”
Section: Methodsmentioning
confidence: 99%
“…Type 2 diabetes (T2D) accounts for the vast majority (around 95%) of these cases, and therefore imposes a substantial economic burden on the French healthcare system [5,6]. The overall healthcare expenditure for people with T2D was estimated at €19.5 billion in 2013, with direct medical costs attributable to T2D and related complications being estimated at €8.5 billion per year [6,7]. The highest individual costs were associated with hospitalizations (33.2% of the total cost) and with medication for diabetes, comorbidities, or other related conditions (23.7% of the total cost).…”
Section: Introductionmentioning
confidence: 99%